Wanita, Wani Ing Tata: a Construction of Javanese Women in Postcolonial Studies - Wasisto Raharjo Jati (Jurnal Perempuan, 2015)
Notion of “wani ing tata” basically is manifestation of noble conception to regard women having dignity in society. That actualization then explained in dual roles which operated in both areas; domestic and social engangement. The words “wanita” basically has been encountered in three social realms such as “wanodya” and “putri”. Those three concepts symbolized multifunctional roles that ascribed women as educator, nurse, and balancer. Javanese women leadership proved by prominent famous figure like Queen Shima, Tribhuana Tungga Dewi, and Suhita. In this case, its conception has ramified into both others notion; ardhaneswari and prameswari. Prameswari can be understood as main women; meanwhile ardhananeswari can be explained as tough and strong women. The emergence of patriarchal system into sociey reduced concept of “wani ing tata”. It puts women as inferior symbolized by “kasur”, “pupur’, and “sumur”.